Pengaruh Tingkat Pendidikan dan Pola Asuh Orangtua Terhadap Prestasi Belajar IPA - Dasmo Dasmo; Nurhayati Nurhayati; Giri Marhento (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2012)
The study was dones in order to prove and verify the influence of parent’s ducation level and parenting style of student’s scisnce learning achievement. The study was conducted at the junior high school students in Kecamatan Periuk, Tangerang, Banten in 2012. The method used in this study is the ekspostfacto a sample of 108 students. From the results obtained: 1) there is the influence of parent’s education level of student’s science learning achievement, 2) there is the influence of parenting style of parents of student’s science learning achievement, and 3) There was no interaction effect of level of education and upbringing of parent of achievement students learn science.